Capsaicin is beneficial to hyperlipidemia, oxidative stress, endothelial dysfunction, and atherosclerosis in Guinea pigs fed on a high-fat diet. (5th January 2019) - Yang, Siyuan; Liu, Lin; Meng, Like; Hu, Xuanyi
Abstract: Capsaicin has anti-inflammatory and antioxidant effects, as well as some benefits on the cardiovascular system. The exact effects of capsaicin on atherosclerosis are poorly understood. To investigate the effects of capsaicin on hyperlipidemia and atherosclerosis in guinea pigs fed on a high-fat diet, as well as its potential mechanisms. Guinea pigs (n = 48) were randomly divided into six groups (n = 8/group): normal diet (control); high fat diet (model); model + low-dose capsaicin (2.5 mg/kg); model + moderate-dose capsaicin (5 mg/kg); model + high-dose capsaicin (10 mg/kg), and model + simvastatin (1.5 mg/kg) (positive control). After 14 weeks, serum lipids, apolipoprotein B100, malondialdehyde (MDA), superoxide dismutase (SOD), nitric oxide (NO), and endothelin-1 were measured. Aortic atherosclerotic lesions were histologically examined. eNOS and iNOS were assessed by immunohistochemistry. The model group developed severe dyslipidemia and associated histologic changes and endothelial dysfunction. All doses of capsaicin decreased total cholesterol, triglycerides, low-density lipoprotein cholesterol, and apolipoprotein B-100, and increased high-density lipoprotein cholesterol (all P  < 0.05). Capsaicin alleviated the plaque area (−17.9–70.5%), plaque area to intima ratio (−18.0–73.6%), and intima thickness (−20.5–83.6%) (all P  < 0.05). Capsaicin decreased MDA (−45.5–76.1%), ET-1 (−19.6–51.6%), and average gray value (AGV) of eNOS (−10.9–48.8%), and increased SOD activity (+31.7–76.1%), NO (+11.2–36.8%), and AGV of iNOS (+6.8-+93.0%) (all P  < 0.05). Similar changes were observed with simvastatin. Capsaicin is beneficial to hyperlipidemia and atherosclerosis in guinea pigs fed on a high-fat diet. Reduced oxidative stress and endothelial dysfunction were involved in these benefits. This could represent a novel approach to prevent cardiovascular diseases. Highlights: Capsaicin decreased cholesterol, TG, LDL-C, and apoB-100, and increased HDL-C. Capsaicin alleviated plaque area, plaque area to intima ratio, and intima thickness. Capsaicin decreased MDA, ET-1, and eNOS. Capsaicin increased SOD activity, NO, and iNOS. Similar changes were observed with simvastatin.